The vindication of absolute idealism - Sprigge, T. L. S. (Timothy Lauro Squire), 1932-2007 (Edinburgh, at the University Press, 1983)
Discusses being as essentially an all-inclusive whole that connects mind, body, and object through identity.
Of consciousness and other things -- Various conceptions of physical reality and their common upshot -- The vindication of panpsychism -- The sentience of the whole and the sentience of the parts -- Relations -- The absolute.
Includes bibliographical references and index.
Keywords: Idealism; Panpsychism; Metaphysics; Consciousness; First philosophy; Metaphysics; Consciousness; Philosophy -- Idealism